THE POSSIBILITY OF THE GOLD STANDARD REINCARNATION - M. D. Kolganova (MGIMO University Press, 2013)
This article provides a chronology of events that led to the crisis of the modern financial system. Also, the author makes an assumption for the further development of global finances. Restoration of the gold standard in a particular seems to be one of these scenarios. The article describes the possible difficulties associated with the restoration of the gold standard in complete or partial form as well as the assumption of the possibility to introduce the gold standard in the framework of the regional integration BRICS.